Labour force management in maritime ports: A comprehensive systematic literature review - Adriana Moros-Daza; Maria Jubiz-Diaz (Heliyon, 2024)
The COVID-19 pandemic led to a labour shortage crisis at maritime ports. Therefore, stakeholders of this industry must have robust tools to maintain good performance indicators of productivity and competitiveness. One of the most critical issues is the labour force related to allocation, performance evaluation, and foreseeing/adapting to new requirements. Many authors have studied the characteristics, elements, trends, and factors crucial in its management. However, there needs to be a comprehensive understanding of this concern. Therefore, this paper aims to develop a systematic literature review on labour force management in the maritime ports to (1) understand the elements and factors that strongly relate to human management and (2) identify future research directions to address the impact of labour shortages. Research questions and keywords were used to search academic databases for peer-reviewed papers, articles, or books. The search, selection and quality assessment processes were performed using the PRISMA methodology. This resulted in 32 documents for review and categorised based on their contributions to the research questions and content. The main findings include factors in labour force management, challenges in optimisation, technology and automation use, methods for evaluating performance, and the impact of the regulatory framework. In addition, potential future research streams were proposed to guide further studies into the needs of this industry.